IMPLEMENTASI KEBIJAKAN IZIN MENDIRIKAN BANGUNAN DI DINAS PENATAAN RUANG DAN PERTANAHAN KOTA PALU - Sadly, Mohamad (Katalogis, 2018)
This aims of finding out the implementation of building permit policy in Department of Spatial Planning and Land affairs of Palu City. The Â writer design a descriptive qualitative. Type of data analysis is primer and secondary. Technique of collecting data., through observation, interview and documentation. Technique of choosing informant by purposive. The data analysis that used are Miles model and Huberman they are data reduction, Data presentation and taking a coclusion. The writer used Van Meter and Van Hornâ€™s theory, that consist of 6 (six) aspect. They are resource policy standard and target, communication between implementing agencies, characteristics of the implementing agency, socio-political and economic conditions, and attitude of executor. According to the research that the implementation of building permit policy. In other case, human resources in controlling the building field still inadequate, and the coordination by Department of Spatial Planning and Land Affair of Palu City to the society that breaking is not strict. So they not awakened public awareness which in turn not obey to the low. The executors attitude do not fair, honest and transparent, because they give the chance to certain part to build the building. Even though that building does not meet technical requirement, but the overall development can be implemented optimally and effectively.